Effects of Dietary Glycine Supplementation on Growth Performance, Immunological, and Erythrocyte Antioxidant Parameters in Common Carp, Cyprinus carpio - Marzieh Abbasi; Ali Taheri Mirghaed; Seyyed Morteza Hoseini; Hamid Rajabiesterabadi; Seyed Hossein Hoseinifar; Hien Van Doan (Animals, 2023)
The effects of dietary glycine supplementation, 0 (control), 5 (5 GL), and 10 (10 GL) g/kg, have been investigated on growth performance, hematological parameters, erythrocyte antioxidant capacity, humoral and mucosal immunity in common carp, Cyprinus carpio. After eight weeks feeding, the 5 GL treatment exhibited significant improvement in growth performance and feed efficacy, compared to the control treatment. Red blood cell (RBC) and white blood cell (WBC) counts, hemoglobin, hematocrit, neutrophil and monocyte counts/percentages, RBC reduced glutathione (GSH) content, and skin mucosal alkaline phosphatase, peroxidase, protease, and lysozyme activities were similar in the glycine-treated fish and significantly higher than the control treatment. Blood lymphocyte percentage decreased in the glycine-treated fish, but lymphocyte count increased, compared to the control fish. RBC glutathione reductase activities in the glycine-treated fish were similar and significantly lower than the control treatment. The highest plasma lysozyme and alternative complement activities were observed in GL treatment. The glycine-treated fish, particularly 5 GL, exhibited significant improvement in RBC osmotic fragility resistance. Dietary glycine had no significant effects on RBC glutathione peroxidase activity, plasma immunoglobulin, eosinophil percentage/count, and hematological indices. In conclusion, most of the benefits of dietary glycine supplementation may be mediated by increased glutathione synthesis and antioxidant power.